UPAYA MENINGKATKAN KEMAMPUAN MENULIS DEVELOPING PARAGRAPH OF EXPLANATION TEXT MELALUI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MATA PELAJARAN BAHASA INGGRIS SISWA KELAS XII IPA 4 SMAN 9 PEKANBARU - Muslainy Muslainy (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2017)
This study is a class action (class action reseach). Based on test results daily writing on students' class XII IPA 4 SMAN 9 Pekanbaru encountered symptoms as follows: only 11 students or 30,55% of the 36 students who have the ability to write a developing Paragraph of explanation textdalam good English so it has reached KKM predetermined is 85. A total of 25 students or 69,4% of the 36 students had difficulty in writing textsehingga developing paragraph of explanation they have not been able to achieve a predetermined KKM. Students find it quickly bored with the lessons presented, it can be seen from their activities are often played or talked with friends when subjects exercised. This study was conducted in two cycles, the data is described is writing developing paragraph of explanation text, ie before the action on the first cycle, the second cycle, each cycle is done in one meeting. This classroom action research in order to work well without barriers obstructing the smooth running of the study, researchers compiled stages traversed in action research, namely: (1) planning/ preparatory actions; (2) Implementation of the action; (3) observation; and (4) reflection. Based on the results of the discussion and analysis as presented in chapter VII can be concluded that the application of the approach contextual teaching and learning (CTL) can improve the ability to write a text explanation developing paragraph of english in english class students of class XII IPA 4 SMAN 9 Pekanbaru. Based on the survey results revealed that developing writing skills of explanation text paragraph british student before action classical gained an average of 64,40 in the first cycle of classical gained an average of 72,50, the second cycle obtain the average classical 90,20.